Exploring experiences of the 2016-2017 cohort of Insourced University of the Witwatersrand residence cleaning and dining hall catering staff. - Mokoena, Thato Naketsi (My University, 2017)
South Africa’s shift into the neoliberalism and the adoption of policies such as Growth Employment and Redistribution in 1996 has resulted in restructuring of the workplace relationship, from permanent forms of employment to outsourcing, privatization and casualization. This nature of work is notorious for its reinforcement of apartheid-like cheap labour and social exclusion of workers. In the late 1990’s and early 2000’s support service workers of the different universities were outsourced to external contractors, thus changing the nature of their previous employment relationship which was permanent. Outsourcing was met with resistance from workers, students, trade unions and different organizations. This led to insourcing of support service staff across universities in South Africa including the University of Witwatersrand in late 2016. The aim of this study was exploring the experiences of the recently insourced University of the Witwatersrand staff who clean the university residences as well as the catering staff at the dining hall on the impact of job security through mechanisms such as insourcing on their livelihoods. Electronic databases including Google, Google Scholar, JSTOR as well as Taylor and Francis were used. The study will follow a qualitative approach which includes semi-structured interviews guided by an interview schedule in an effort to get detailed accounts of their perspectives. The prospective participants who are dining hall and cleaning staff previously employed by Ukweza or Royal Mnandi will be recruited using purposive sampling. Data collected from participants was thematically analysed with the purpose of extracting prevalent themes within, which captured the perspectives of the recently insourced workers at University of the Witwatersrand in a meaningful way. Dissemination of the study will be electronic and in the form of print, research report and prospective publication. The study was presented to the University of the Witwatersrand’s Department of Social work. Key words: insourcing, outsourcing, exploitation, livelihoods, support services, University of Witwatersrand
Proposal for research submitted to The Department of Social Work in the School of Human and Community Development in partial fulfilment of requirements for Honours in Social Work.